STUDY OF THE SYSTEM OF CYTOKINES IN CASE OF HERPETIC AND CHLAMYDIA-HERPETIC INFECTION - E.V. Markelova (Journal of Global Pharma Technology, 2016)
The levels of TNF-α, TFN-β, IFNγ and IL-10 in the venous blood serum and the ejaculate from 80 men with sexually transmitted infections – the main group (MG) were studied. All men of OG were divided into 2 groups: 40 men with chronic viral urethritis (genital herpes – herpetic urethritis (HU)) and 40 men with viral-bacterial urethritis (genital herpes in conjunction with clamidiosis – herpetic-chlamydial urethritis (HCU)). The comparison group (control group) consisted of 20 apparently healthy male volunteers. More pronounced disorders of local and systemic immunity in the group of men with urethritis of viral and bacterial origin were found in both in venous blood serum and in the ejaculate. Keywords: cytokines, ejaculate, herpes, clamidiosis.